Bimbingan dan Konseling Kelompok Berbasis Shalat dalam Mereduksi Perilaku Prokrastinasi: Studi pada Santri Pesantren Al-Manar Kecamatan Krueng Barona Jaya - Azhari, Azhari (Jurusan Bimbingan dan Konseling Islam, 2021)
Prayer is a compulsory recommendation for Muslims and Muslim women, especially those who are converted. Through the prayer movement, humans are also able to grow the body's performance power. This performance power of the body is found in the prayer movements ranging from standing upright, takbiratul ihram, bowing, i`tidal, prostration, sitting between two prostrations, the final takhiyatul movement to greeting. In this study, it focuses on how to form new behavior with a prayer-based group guidance and counseling approach to reduce procrastination behavior in Al-Manar pesantren students. The objectives of this study include: (1) To determine the procrastination behavior of the Al-Manar Islamic boarding school students. (2) To determine the factors that cause procrastination behavior and (3) To determine the implementation of prayer-based group guidance and counseling in reducing procrastination behavior in Al-Manar pesantren students. The approach method in this research uses interpretive methods with data collection techniques through: observation, document analysis and interviews. And the results of the study illustrate that there are a number of changes in a comprehensive cognitive, affective and psychomotor perspective for the better.